Islamic Higher Education as a Part of Kazakhs’ Cultural Revival - Mustafayeva, Anar; Paltore, Yktiyar; Pernekulova, Meruyert; Issakhanova, Meirim (Journal of Ethnic and Cultural Studies, 2023)
Kazakhstan is currently going through a phase of national and cultural renaissance. This began in the 90s when political and spiritual independence had been obtained. The process of national or cultural revival entails a shift in the paradigm, a reevaluation of prior ideas, and a return to long-forgotten customs, beliefs, or traditions that are distinctive to contemporary Kazakhstani culture. Undoubtedly, a return to religious origins via freedom from the burden of the Soviet ideology of atheism and the expansion of Islamic education is the fundamental trend in the development of national-cultural awareness. Kazakhstan has experienced a spiritual vacuum because of the rapid shift from the ban on religion to religious freedom. This has resulted in a surge in the number of religious denominations and religious organizations in the nation and the emergence of radical movements. The issue is particularly significant for the post-USSR nations that are now experiencing hardships. Evidence of this is shown in two ways: (1). many people in the CIS countries have begun to show a keen interest in religious values and traditions, and (2). new sociopolitical and socio-cultural realities brought about by the fall of communism and the dissolution of the USSR have sparked the growth of national consciousness and altered spiritual guiding principles in the post-Soviet society, particularly in Kazakhstani society. The establishment of relations with the Muslim and non-Muslim world has incorporated the opening of borders, allowed missionaries to enter freely, and allowed current citizens to go abroad for religious education and general education in both religious and non-religious-oriented countries. In addition, the liberal legislation in relation to religion in general in the early 2000s opened up new horizons for representatives of religious and pseudo-religious communities. Therefore, religious education, namely Islamic, given that population of the state is predominantly Muslim, is an absolute necessity.